Search for ZZ and ZH production in the bbb¯ b final state using ¯proton-proton collisions at √s = 13 TeV - CMS,Collaboration (European Physical Journal C: Particles and Fields, 2024)
A search for ZZ and ZH production in the bbb¯ b¯final state is presented, where H is the standard model (SM)Higgs boson. The search uses an event sample of proton-proton collisions corresponding to an integrated luminosityof 133 fb−1 collected at a center-of-mass energy of 13 TeVwith the CMS detector at the CERN LHC. The analysis introduces several novel techniques for deriving and validating amulti-dimensional background model based on control samples in data. A multiclass multivariate classifier customizedfor the bbb¯ b final state is developed to derive the background ¯model and extract the signal. The data are found to be consistent, within uncertainties, with the SM predictions. Theobserved (expected) upper limits at 95% confidence level arefound to be 3.8 (3.8) and 5.0 (2.9) times the SM predictionfor the ZZ and ZH production cross sections, respectively.